Anaplerosis in cancer: Another step beyond the warburg effect - Ochoa-Ruiz, Estefania; Diaz-Ruiz, Rodrigo (Scientific Research Publishing, 2016)
Biosynthesis is up-regulated in tumors and thus the demand for anabolic intermediates is increased. The metabolic routes providing the building blocks for macromolecules are thus a very attractive target as they are not normally up-regulated in a normal quiescent cell. Some routes for glycolysis-derived intermediates production have been identified, but these do not constitute the whole pool of biosynthetic molecules in the cell, as many of these derive from mitochondria in the Krebs cycle. Indeed, this metabolic pathway is considered a “biosynthetic hub” from which anabolism is fed. If a metabolite efflux is indeed occurring, anaplerotic reactions must keep a steady supply of substrates. In spite of this obvious relevance of anaplerosis, it has been poorly characterized in the malignant cell context. Glutaminolysis and and pyruvate carboxylation are two pathways that function in an anaplerotic fashion. In spite of the increasing evidence implicating these two processes in cancer metabolism their role as intermediate providers is overlooked. In this review we analyze the implications of an active anaplerosis in cancer and we discuss experimental evidence showing the relevance of these metabolic routes in tumor physiology.
Keywords: Anaplerosis; Biosynthesis; Cancer; Glutaminase; Krebs Cycle; Metabolism; Mitochondria; Pyruvate Carboxylase; Warburg Effect